Prevalence and magnitude of preseason clinically-significant single-leg balance and hop test asymmetries in an English adult netball club. (November 2019) - Clark, Nicholas C.; Mullally, Elaine M.
Abstract: Objectives: Side-to-side asymmetry of lower-limb motor-performance is associated with increased noncontact injury risk in agility-sports. Side-to-side symmetry-analyses using single-leg balance and hop tests has not been reported for community-level adult netball players. The purpose of this study was to perform preseason side-to-side symmetry-analyses using eyes-closed-balance (ECB), triple-hop-for-distance (THD), single-hop-for-distance (SHD), and vertical-hop (VH) tests. Design: Cross-sectional; Setting: Community-level adult netball club. Participants: Twenty-three female players (age 28.7 ± 6.2yr; height 171.6 ± 7.0 cm; mass 68.2 ± 9.8 kg). Main outcome measures: Right-left group-level comparisons (paired t -test) and individual-level comparisons (absolute-asymmetry (%)). A limb symmetry index was calculated for each test and a clinically-significant absolute-asymmetry defined as >10%. Clinically-significant absolute-asymmetry prevalence (%) was computed for each test. Results: There were no right-left significant differences for any test. Maximum absolute-asymmetries for the ECB, THD, SHD, and VH were 93.3%, 15.2%, 16.7%, and 60.3%, respectively. The prevalence of clinically-significant absolute-asymmetries for the ECB, THD, SHD, and VH was 91.3%, 8.7%, 8.7%, and 52.2%, respectively. Conclusions: Group-level comparisons with statistical tests fail to expose the extent of clinically-significant absolute-asymmetries. Most players demonstrated preseason clinically-significant absolute-asymmetries for the ECB and VH tests. Preseason clinically-significant absolute-asymmetries that may predispose increased lower-limb noncontact injury risk are widespread in a community-level adult netball club. Highlights: Group-level statistics fail to expose preseason clinically-significant asymmetries. Most players had clinically-significant asymmetry for the eyes-closed-balance test. Most players had clinically-significant asymmetry for the vertical-hop test. Clinically-significant asymmetry is widespread in a community-level adult netball